Enhancing Motivation for Oral Hygiene Implementation among Immobilized Compos Mentis Patients through The Development of a Dental Care Table in Inpatients Settings - Mokhamad Ainu Roziq; Sukini Sukini; Diyah Fatmasari (International Journal of Advanced Health Science and Technology, 2024)
Brushing teeth is one way to maintain oral hygiene. Implementation of tooth brushing with oral hygiene protocols in hospitalized patients in addition to avoiding infection can also improve the quality of life of patients during treatment. There are often cases of neglected oral hygiene in hospitalized patients. This is due to the limitation of movement (immobilization) in patients to carry out these activities. Often the appearance of discomfort when using supporting infrastructure in the room such as basins. Dental care table (DCT) is an idea in supporting the implementation of oral hygiene while in bed. Interest in the latest innovations is expected to encourage the motivation of immobilized patients with compost mentis to carry out oral hygiene activities that have been carried out at home. This study aims to determine the description of the motivation for implementing oral hygiene for immobilized patients with kompos mentis in the inpatient installation . This type of research with Research and Development (R&D) and pre-experiment research (Pretest and Posttest group design) with purposive sampling technique obtained 32 respondents. The method of measuring product feasibility uses David Garvin's "Eight Dimensions of Quality" test with 32 questions, while measuring motivation using TSRQ (Treatment Self Regulation Quetionnaire) with 12 questions. At the research stage with information gathering to informants and observation. Followed by designing product builds tailored to the needs and study of patient characteristics according to anthropometric data based on ergonomic principles, then proposed to experts. The next stage is through testing and measuring the feasibility score. The completed product improvement stage is tested again until it is declared feasible. Before the trial on the patient, a measurement of motivation to implement oral hygiene on the patient was carried out to obtain a pretest value of motivation. Then the trial use of the product and finally evaluate the value of the oral hygiene implementation motivation score. The feasibility data analysis technique uses Aiken V and ICC, to test the difference in motivation scores using the Wilcoxon test. The results showed that the Dental care table (DCT) was feasible with a score of 85.16%, with an ICC score of 0.958. Increased motivation to implement oral hygiene for immobilized patients with compost mentis in the inpatient installation from 74.93% to 80.60% with a significance value of 0.046 (p-value <0.005). Immobilized patients with mentis compost have motivation in the strong motivation category, with a motivation score value between 67% - 100%.